Academic Librarians Perceive Duration and Social Interaction as Important Elements for Professional Development - Bussell, Hilary (Evidence Based Library and Information Practice, 2018)
A Review of: Attebury, R. I. (2017). Professional development: A qualitative study of high impact characteristics affecting meaningful and transformational learning. The Journal of Academic Librarianship, 43(3), 232-241. http://dx.doi.org//10.1016/j.acalib.2017.02.015 Abstract Objective – To understand the characteristics of meaningful and transformational professional development experiences of academic librarians. Design – Qualitative analysis of in-depth interviews using a hermeneutic phenomenological approach. Setting – Public and private colleges and universities in the United States of America. Subjects – 10 academic librarians. Methods – The researcher selected 10 participants using an initial survey distributed through national library electronic mail lists. Two rounds of semi-structured, in-depth interviews were conducted over Skype during fall 2014 and spring 2015. The first round of interviews began with background questions about participants’ careers, then moved on to questions about professional development experiences that were meaningful and/or transformational. The responses from this first round of interviews were used to develop questions for a second round of interviews with the same participants. After completing the interviews, the researcher sent follow-up emails to participants in order to gather feedback on summaries and interpretations of interviews. The transcribed interviews were used to create an initial set of codes and then imported into NVivo for analysis using a hermeneutic phenomenological approach. Main Results – All participants reported on professional development experiences that they found to be meaningful. Half of the participants discussed professional development experiences that were transformational for their perceptions and practice of librarianship. The themes of duration and interaction were identified in every participant’s discussions of meaningful or transformational professional development. Reflection, discomfort, and self-awareness were also identified as prominent themes. Conclusion – The study found that two of the most important ingredients for meaningful and transformational professional development are activities that are sustained over time and that include social interaction. The participants perceived long-term, interactive professional development activities as opportunities to identify and address gaps in their professional knowledge, which benefits themselves and their organizations. On-the-job learning, single-theme workshops or institutes, and professional committee work were particularly promising forms of meaningful professional development. The author recommends that academic librarians who are interested in meaningful or transformational professional development look for activities that are sustained and interactive, that promote reflection, and that provide opportunities to increase self-awareness of gaps in knowledge. Facilitators of professional development activities should include interactive components and ensure that participants have a chance to stay in contact after the event in order to encourage long-term interaction and reflection.